Follicular Cholecystitis: Reappraisal of Incidence, Definition, and Clinicopathologic Associations in an Analysis of 2550 Cholecystectomies. (December 2020) - Saka, Burcu; Memis, Bahar; Seven, Ipek Erbarut; Pehlivanoglu, Burcin; Balci, Serdar; Bagci, Pelin; Reid, Michelle; Dursun, Nevra; Escalano, Oscar Tapia; Roa, Juan Carlos; Araya, Juan Carlos; Kong, So Yeon; et al.
Context: Follicular cholecystitis (FC) is a poorly characterized entity. Objective: To determine its frequency/clinicopathologic associations. Design: A total of 2550 cholecystectomy specimens were examined. Two hundred three of these were consecutive routine cholecystectomies submitted entirely for microscopic examination to determine the relative frequency of incidental pathologies in gallbladders (GBs). The remainder had representative sampling. Underlying conditions were nonobstructive pathologies (1270 nonspecific cholecystitis), obstructive (62 distal biliary tract tumors, 35 primary sclerosing cholangitis, and 31 autoimmune pancreatitis), and neoplastic (n = 949). FC was defined as 3 distinct lymphoid follicles (LFs)/centimeter. Results: In the GBs totally submitted for microscopic examination, the true frequency of FC was found to be 2.5% (5/203), and in the representatively sampled group, it was 1.9%, with similar frequencies in nonobstructive, obstructive, and neoplastic cases (2.3%, 3.1%, and 1.3%, respectively, P = .77). When the 39 FC in nonneoplastic GBs contrasted with ordinary chronic cholecystitis, they were associated with older age (68 vs 49 years, P < .0001), similar gallstone frequency (68 vs 81%), female/male ratio (2.7 vs 2.6), and wall thickness (4 mm for both). None had lymphoma/parasites/ Salmonella infection. Of 17 cases who had undergone gastric biopsy, 5 had chronic gastritis (2 with Helicobacter pylori ). Microscopically, the LFs were the main inflammatory process often with minimal intervening inflammation. IgG4-positive plasma cell density was low (<10/high-power field) in 21/24(87.5%) cases. Conclusions: Follicular cholecystitis is seen in 2% of cholecystectomies, typically in significantly older patients, suggesting a deranged immune response. A third of the patients reveal biopsy-proven gastritis. FC does not seem to be associated with autoimmunity, lymphoma, or obstructive pathologies.